Comparative Inventory of Rock Glaciers and Permafrost Lower Limits in Api Nampa, Manaslu and Kanchenjunga Region (The Geographic Base, 2024)
Rock glaciers are cryogenic landforms that contain surface rock debris that encloses an ice-core or ice-cemented debris mixture. A study of rock glacier dynamics is useful to understand the effect of global warming. This study provides inventories of rock glaciers, along with their status, and delineates the Lower Limit of Permafrost in three areas in Eastern, Central, and Western Nepal. Those are the Api Nampa Conservation Area (ANCA), Manaslu Conservation Area (MCA) and Kanchenjunga Conservation Area (KCA). Freely accessible Google Earth Pro's images were used to map the rock glaciers. A total of 340 Rock Glaciers (RGs) with a total area of 76.21 km2 were identified between elevations of 3821 to 5667 meters above sea level (masl). The highest rock glacier concentration was identified between 4800 – 5200 masl. Mean elevations of RGs are 4703.93 masl, 4903.79 masl, and 4928.14 masl in ANCA, MCA, and KCA, respectively. There is a downward trend in the elevation of the rock glacier while moving from the Eastern Nepal Himalaya to the Western Nepal Himalaya. Comparing all three conservation areas, it has been seen that intact RGs are predominantly found above 4800 masl and relict RGs below it. Northern slopes have more RGs in ANCA, while southern slopes have much of it in MCA and KCA. RGs in the South-facing slope area are found at much higher altitudes, with most being debris and intact. In contrast, the majority of RGs from northern aspects are intact and the talus. Using RGs as a proxy for permafrost, it is estimated that the Lower Limit of Permafrost (LLP) of ANCA, MCA, and KCA were 4630 masl, 4324 masl, and 4417 masl, respectively. The mean elevation of RGs is high in MCA and KCA, but LLP is lower than ANCA. This difference may be attributed to the presence of sporadic permafrost or isolated patches.